Biotechnological potential of exopolysaccharide as a bioemulsifier produced by Rhizobium radiobacter CAS isolated from curd. (October 2019) - Kavitake, Digambar; Marchawala, Farhat Zakirhusain; Delattre, Cedric; Shetty, Prathapkumar Halady; Pathak, Hilor; Andhare, Prasad
Abstract: Succinoglycan exopolysaccharide (EPS) from Rhizobium radiobacter CAS and its rheological behavior has been studied earlier. In present investigation the emulsifying potential of CAS EPS has been determined. CAS EPS concentration was optimized with hydrocarbons soybean oil and n-Hexane, whereas effect of pH (3.0–11.0), salinity, monovalent ions, divalent ion, (NaCl, KCl and MgCl2 ), freezing/thawing, temperature heating, emulsion stability and rheology on emulsifying activity (EA) was inspected using n-Hexane, paraffin oil, groundnut oil and soybean oil. CAS biopolymer represented superior emulsion stabilization ability (100%) under stress conditions and was highly tolerant to extreme pH, inorganic salts concentrations. Thermal stability of emulsions has found 100% at −20 °C–40 °C, whereas, at temperature 50 °C–120 °C high emulsion index (82.4–94.1% respectively) were recorded. Wetting filter paper test verified oil-in-water (o/w) type emulsion whereas rheological property showed pseudoplastic nature of emulsions. During stability of emulsions up to 30 days, some reduction of emulsification activity was observed for paraffin oil, however CAS hydrocolloid formed 100% emulsion index for n-Hexane, groundnut and soybean oils. These emulsifying and better hydrophilic physical properties make CAS hydrocolloid a prospective alternative to commercial biopolymers and chemical surfactants. Graphical abstract: Image 1 Highlights: CAS EPS showed high emulsifying activity with different hydrocarbons. CAS EPS emulsions are highly stable at extreme conditions of pH, temperature and salts. Rheology studies revealed pseudoplastic nature of emulsions. Emulsion stability was detected up to 30 days.